Brasil, Argentina e a questão cubana (1959-1964): quando a independência faz a união - Botega, Leonardo da Rocha (2009)
The historical moment in which Brazil and Argentina passed through, at the same time, the experience of independent external politics of the Argentine President Arturo Frondizi (1961-1964), and the Brazilian Presidents, Jânio Quadros and João Goulart (1961-1964), has established a decisive time for the international relations between these countries. Through the circumstances of that time, common points were the principle of autodetermination of the peoples and non-interference, the national developmentism, the international trade relations, the discussion about the exchange rate growing worse, the hankering for industrialization, and the being sought after Latin America integration. So, the independent external politics stood as the main base for getting both of these countries nearer. Such unit and its independent external politics of both Brazil and Argentina had undergone an ultimate test, the Cuban Question. Acting against to it, the United States government, as the president Dwight Eisenhower as the president John Kennedy later, sought how to put it into the Inter-American system boundary lines, defining it as opposed to this. From this definition, they got to impose sanction or even to militarily intervene on the Caribbean island. Notwithstanding the external or internal pressure, as Arturo Frondizi government of Argentina as Jânio Quadros and João Goulart government of Brazil stood to their independent position reaffirming the principles of non-intervention and auto-determination of the peoples, as well as defending the international right. The highlight was the tensest of this time, the VIII Reunião de Consulta dos Ministros de Relações Exteriores da Organização dos Estados Americanos, held in Punta Del Este, Uruguai, from January 23 to 30, 1962, the last act together by external politics of Argentina and Brazil independently.